Emerging styles of governance a global context - Ellison, Kenneth H. (1998)
The Philippines is the center of some of the richest experiments exploring new ways of governing based on decentralization, local autonomy and large-scale participation of the nongovernmental community in democratic processes. This is an attempt to provide a sense of various shifts taking place in global governance, in order to place these Filipino experiments in a wider context of global change.
Keywords: Decentralization; Governance